PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR, KNOWLEDGE SHARING, DAN AUTHENTIC LEADERSHIP TERHADAP KINERJA KARYAWAN DALAM PERSPEKTIF MANAJEMEN SUMBER DAYA INSANI (STUDI PADA KARYAWAN PKS SELAPAN JAYA PT. SAMPOERNA AGRO TBK) - Rika Fahrinta; Ahmad Habibi; Muhammad Kurniawan (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the influence of organizational citizenship behavior, knowledge sharing and authentic leadership on employee performance in Selapan Jaya-PT.Sampoerna Agro Tbk PKS employees, in the perspective of human resource management. This research uses a quantitative approach with data collection through questionnaires with a sample of 62 people. The data analysis technique uses Partial Least Square (SmartPLS version 4). The results showed that: (1) Organizational Citizenship Behavior has a positive and significant effect on Employee Performance. (2) Knowledge Sharing has a positive and significant effect on Employee Performance. (3) Authentic Leadership has a positive and significant effect on Employee Performance.